Heritage to health: The socio-cultural and health impacts of traditional ethnic foods in Saudi Arabian society - M. Amin Mir; Duaa Hefni; Neha Chauhan (Food Chemistry Advances)
The nutritional assessment of traditional foods is essential for precisely determining dietary intakes because they constitute a substantial portion of the average Saudi Arabian population's diet. Thus, the purpose of this study is to evaluate the nutritional value of 25 traditional meals that are widely consumed in Saudi Arabia. The study concentrated on the quantities of vitamin D, calcium, phosphorus, iron, phytate, and oxalate as well as the proximate composition. The food items under analysis had 1.32–10.5 % protein, 1.14–14.14 % fat, 3.67–6.20 % carbohydrate, 1.16–3.15 % dietary fiber, 0.52–5.24 % ash, and 5.11–109.21 g moisture content on a fresh weight basis. The range of vitamin B content in g was 0.01–0 .87 g. Calcium, iron, and sodium had respective mineral contents (mg/100 g) of 1.02–23.13, 0.07–2.12 mg, and 1.00–45 mg. The concentrations of oxalate and phytate (mg/100 g) were 1.02–48.63 mg and 3.15–71.13 mg, respectively. We also looked at the connection between the prevalence of diabetes in Saudi Arabia and the intake of these foods. According to the study, traditional Saudi meals are a wonderful source of healthful Carbohydrate since they are frequently eaten whole grain, which makes them high in fiber, certain vitamins, and minerals. Furthermore, the majority of traditional Saudi foods have a glycemic index (GI) in the low range. These foods may be beneficial for postprandial glycemic and insulinemic responses due to their decreased GI and glycemic load. Given Saudi Arabia's high diabetes prevalence, these advantageous qualities of traditional Saudi foods could greatly enhance dietary management and prevent diabetes mellitus.